Virtual Submerged Floating Operational System for Robotic Manipulation. (12th November 2018) - Zhang, Qin; Zhang, Jialei; Chemori, Ahmed; Xiang, Xianbo
Abstract : In this work, a virtual submerged floating operational system (VSFOS) based on parallel and serial robotic platforms is proposed. The primary aim behind its development lies in carrying out simulated underwater manipulation experiments in an easier and safer way. This VSFOS is consisted of a six-degree-of-freedom (6-DOF) parallel platform, an ABB serial manipulator, an inertial sensor, and a real-time industrial computer. The 6-DOF platform is used to simulate the movement of an underwater vehicle, whose attitude is measured by the inertial sensor. The ABB manipulator, controlled by the real-time industrial computer, works as an operational tool to perform underwater manipulation tasks. In the control system architecture, software is developed to receive the data collected by the inertial sensor, to communicate and send instructions. Furthermore, the real-time status of the manipulator is displayed in this software. To validate the proposed system, two experiments have been conducted to test its performance. In the first experiment, the test is carried out to check the communication function of VSFOS, while in the second one, the manipulator is intended to follow the movement of the parallel platform and perform simulated operational task in the space. The obtained results from these two experiments show clearly the effectiveness and the performance of the proposed VSFOS.